First investigation of genetic control of meiosis in sugarcane - Soares, Nina Reis (2023)
Sugarcane (Saccharum spp.) has one of the most complex crop genomes. Modern varieties are highly polyploids and aneuploids, resulting from interspecific hybridization between Saccharum officinarum and S. spontaneum. Research on the meiotic control in polyploid species is limited, with the exception of wheat Ph1 locus, carrying the meiotic gene ZIP4 (TaZIP4-B2) that promotes pairing and synapsis between homologues, whilst suppressing CO between homoeologous chromosomes. In sugarcane, despite its interspecific origin, bivalent association is favored, and multivalents, if they occur, are resolved at the end of meiosis I. Our aim here was to investigate the supposedly control of synapsis in sugarcane. We have investigated the ZIP4 gene and performed the immunolocalization of meiotic proteins, namely the synaptonemal complex proteins ZYP1 and ASY1. The sugarcane ZIP4 gene is located on chromosome 3 and it is expressed more abundantly in flowers, showing a similar profile to that of TaZIP4-B2. The expression level of ZIP4 is higher in S. spontaneum, an evolving autopolyploid, and less expressed in S. officinarum, a legitimate octaploid species. The ZIP4 protein contains a TPR domain, essential to its scaffolding function, and the 3D structure prediction is highly similar to that of TaZIP4-B2. The immunolocalization of the ASY1 and ZYP1 proteins revealed that S. officinarum completes synapsis. However, in S. spontaneum and SP80-3280, a modern variety, no nuclei with complete synapsis were observed. Our results will have implications for sugarcane genetic mapping and genomics, whose understanding of inheritance and genome organization remain somewhat obscure.